Relationship Between the Length and Depth of Myocardial Bridging and the Degree of Proximal Coronary Artery Stenosis Using Coronary Computed Tomography Angiography - Teodorus Alfons Pratama; Rusli Muljadi; Koesbandono Koesbandono; Antonia Anna Lukito; Andree Kurniawan (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Myocardial bridging (MB) is a congenital anomaly of the coronary arteries that results in dynamic compression during the cardiac cycle. This condition accelerates the development of atherosclerosis, particularly in the proximal coronary segment. Evidence regarding the relationship between MB morphology and the degree of stenosis based on coronary CT angiography (CCTA) remains limited and inconsistent. This study aimed to evaluate the association between MB length and depth and the degree of proximal coronary artery stenosis using CCTA at Siloam Lippo Village Hospital. Methods: This was an observational analytic study with a cross-sectional design. Samples were obtained through consecutive sampling of patients aged ≥18 years who underwent CCTA between 2024 and 2025. Data were analysed using the Mann-Whitney U test for comparison of means, with a p-value <0.05 considered statistically significant. Result: A total of 144 patients met the inclusion criteria. MB was most commonly found in the mid-left anterior descending (mid-LAD) segment, with a mean depth of 1.18 mm and a mean length of 14.67 mm. Most proximal stenosis cases were categorized as non-significant (<50%). Mann-Whitney U analysis showed that MB depth was significantly associated with the degree of proximal stenosis (p = 0.006), whereas MB length was not (p = 0.345). The interaction between these variables, represented as MB area, showed a stronger correlation with the degree of stenosis (p = 0.004). Conclusion: MB is associated with the degree of proximal coronary artery stenosis as assessed by CCTA. These findings may improve risk stratification and support more appropriate clinical management in patients with MB.